The Agile Concept in Enhancing a More Responsive Organization - Permatasari, Retno Japanis (JAKI : Jurnal Akuntansi, 2024)
In the modern business landscape, organizations must navigate rapidly changing environments to maintain competitiveness and relevance. The Agile concept, initially developed for software development, has since been adopted across diverse industries to enhance organizational flexibility and responsiveness. This paper explores the application of Agile methodologies in improving organizational adaptability. The study employs a qualitative approach, reviewing existing literature, case studies, and examples of organizations that have successfully implemented Agile practices outside of software development. Through this method, the research highlights how Agile principles—such as flexibility, transparency, and iterative planning—can be utilized to foster cross-functional collaboration, accelerate decision-making, and enable organizations to respond quickly to market changes. Additionally, the paper discusses the cultural shifts required to implement Agile, including the breakdown of traditional hierarchical structures and the promotion of self-organizing teams. By integrating continuous feedback loops and customer-centric approaches, Agile supports more dynamic, responsive operations. Case studies across various industries demonstrate the real-world benefits of adopting Agile for enhancing organizational responsiveness, improving customer satisfaction, and increasing innovation. The findings suggest that organizations that embrace Agile are better equipped to navigate uncertainties and capitalize on new opportunities in a fast-paced, competitive environment.